Noncanonical PD-1/PD-L1 Axis in Relation to the Efficacy of Anti-PD Therapy - Long, Yiru; Yu, Xiaolu; Chen, Runqiu; Tong, Yongliang; Gong, Likun (Frontiers in Immunology, 2022)
With programmed death 1/ligand 1 (PD-1/PD-L1) as the cornerstone, anti-PD antibodies have pioneered revolutionary immunotherapies for malignancies. But most patients struggled to respond to anti-PD owing to primary or acquired resistance or even hyperprogression, pointing to more efforts needed to explore this axis. PD-1 constrains T-cell immunoreactivity via engaging with PD-L1 of tumor/myeloid cells is the canonical PD-1/PD-L1 axis function mode. Studies are increasingly aware of the impact of noncanonical PD-1/PD-L1 expression in various cancers. PD-L1 induced on activated T-cells ligates to PD-1 to mediate self-tolerance or acts on intratumoral myeloid cells and other T-cells, affecting their survival, differentiation and immunophenotyping, leading to tumor immunosuppression. Myeloid PD-1 interferes with their proliferation, differentiation, cytokine secretion and phagocytosis, mediating remarkable pro-tumor effects. Tumor cell intrinsic PD-1 signaling has diverse functions in different tumors, resulting in pro-proliferation or proliferation inhibition. These nonclassical PD-1/PD-L1 functions may be novel anti-PD mechanisms or causes of treatment resistance. This review highlights the nonnegligible role of T-cell-intrinsic PD-L1 and tumor/myeloid PD-1 in the cell interplay network and the complex impact on the efficacy of anti-PD antibodies. Reconsidering and rational utilization of the comprehensive PD-1/PD-L1 axis could cumulate breakthroughs in precision treatment and combination for anti-PD therapies.